2008
DOI: 10.1007/s10695-008-9264-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fish oil replacement with lard and soybean oil affects triacylglycerol and phospholipid muscle and liver docosahexaenoic acid content but not in the brain and eyes of surubim juveniles Pseudoplatystoma sp.

Abstract: Triplicate groups of juvenile suribim were fed for 183 days one of four different isonitrogenous (47.6% crude protein) and isolipidic (18.7% lipid) diets formulated using three different lipid sources: 100% fish oil (FO, diet 1); 100% pig lard (L, diet 2); 100% soybean oil (SO, diet 3), and FO/L/SO (1:1:1, w/w/w; diet 4). The tissue levels of fatty acids 18:2n-6 and 18:3n-3 decreased relative to corresponding dietary fatty acid values. The 20:5n-3 and 22:6n-3 composition of muscle and liver neutral lipids were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
(42 reference statements)
0
11
0
1
Order By: Relevance
“…Other studies have reported that fillet and liver tissues are more directly influenced by fatty acid intake than brain, eye, and similar tissues in which the conservation of fatty acid profile is essential for maintaining structural or physiological competence (Noffs et al 2009;Gause and Trushenski 2013;Trushenski et al 2013a;Woitel et al 2014). Fatty acid deficiencies have been linked to impaired vision in fish (Bell et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that fillet and liver tissues are more directly influenced by fatty acid intake than brain, eye, and similar tissues in which the conservation of fatty acid profile is essential for maintaining structural or physiological competence (Noffs et al 2009;Gause and Trushenski 2013;Trushenski et al 2013a;Woitel et al 2014). Fatty acid deficiencies have been linked to impaired vision in fish (Bell et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The limited amount of work performed to date has suggested that dietary DHA and EPA had different efficiency in influencing bio‐functions of fish such as vision (Navarro, McEvoy, Bell, Amat, Hontoria & Sargent ; Noffs et al . ), pigmentation (Villalta et al . ; Vizcaíno‐Ochoa et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, its importance was relatively neglected compared to the total amount of n-3 LC-PUFAs (Sargent, Bell, Mcevoy, Tocher & Estevez 1999;Kim, Lee, Park, Bai & Lee 2002;Lee, Lee & Kim 2003;Skalli & Robin 2004;Hamre & Harboe 2008;Wilson 2009;Lund & Steenfeldt 2011;ØStbye, Kjaer, Rør a, Torstensen & Ruyter 2011;Zuo, Ai, Mai, Xu, Wang, Xu, Liufu & Zhang 2012b). The limited amount of work performed to date has suggested that dietary DHA and EPA had different efficiency in influencing bio-functions of fish such as vision (Navarro, McEvoy, Bell, Amat, Hontoria & Sargent 1997;Noffs et al 2009), pigmentation (Villalta et al 2008;Vizca ıno-Ochoa et al 2010) and reproduction (Mazorra, Bruce, Bell, Davie, Alorend, Jordan, Rees, Papanikos, Porter & Bromage 2003), whereas little information was available regarding the difference between DHA and EPA in modulation of fish health such as immunity and stress resistance (Wu, Ting & Chen 2003;Zuo, Ai, Mai, Xu, Wang, Xu, Liufu & Zhang 2012a). Most comparison studies on immunomodulatory activities of fatty acids focused on the n-3/n-6 ratio (Chow, Sisfontes, Bj€ orkhem & Jondal 1989;Bell, Ashton, Secombes, Weitzel, Dick & Sargent 1996;Thompson, Tatner & Henderson 1996;Farndale, Bell, Bruce, Bromage, Oyen, Zanuy & Sargent 1999;Lauridsen, Stagsted & Jensen 2007;Berge, Witten, Baeverfjord, Vegusdal, Wadsworth & Ruyter 2009), and the previous studies on fatty acids were primarily conducted in larvae, which were not appropriate targets for immunity study.…”
Section: Introductionmentioning
confidence: 99%
“…Also in a Pseudoplatystoma sp. , growth performance was unaffected in fish fed with fish oil, lard, soya bean or a blend of these three lipid sources (Noffs et al, ). In P. fasciatum, growth performance was also unaffected by using cod liver oil, esters of linoleic and linolenic acids, or a blend of olive oil and linseed oil; however, the performance was improved by using soy–lecithin as lipid source (Arslan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, no difference in growth performance was observed in P. coruscans fed diets including lard, corn oil, soya bean oil or linseed oil as the unique lipid sources (Martino et al, 2002b). Also in a Pseudoplatystoma sp., growth performance was unaffected in fish fed with fish oil, lard, soya bean or a blend of these three lipid sources (Noffs et al, 2009). In P. fasciatum, growth performance was also unaffected by using cod liver oil, esters of linoleic and linolenic acids, or a blend of olive oil and linseed oil; however, the performance was improved by using soylecithin as lipid source (Arslan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%